Portrait Painting in the Works of Pavel Philonov. From Realism to Naturalism - Furman, Olga V. (Actual Problems of Theory and History of Art, 2013)
This article proposes a stylistic classification of Pavel Philonov’s portrait works within the framework of his analytic art system. Special attention is given to his graphic work called “Family Portrait” (1924, The Russian Museum) and its interpretation.